Replication of MERS and SARS coronaviruses in bat cells offers insights to their ancestral origins. Issue 1 (December 2018) - Lau, Susanna; Fan, Rachel; Luk, Hayes; Zhu, Longchao; Fung, Joshua; Li, Kenneth; Wong, Emily; Ahmed, Syed; Chan, Jasper; Kok, Raven; Chan, Kwok-Hung; Wernery, Ulrich; et al.
Abstract Previous findings of Middle East Respiratory Syndrome coronavirus (MERS-CoV)-related viruses in bats, and the ability ofTylonycteris -BatCoV HKU4 spike protein to utilize MERS-CoV receptor, human dipeptidyl peptidase 4 hDPP4, suggest a bat ancestral origin of MERS-CoV. We developed 12 primary bat cell lines from seven bat species, includingTylonycteris pachypus, Pipistrellus abramus andRhinolophus sinicus (hosts ofTylonycteris -BatCoV HKU4, Pipistrellus -BatCoV HKU5, and SARS-related-CoV respectively), and tested their susceptibilities to MERS-CoVs, SARS-CoV, and human coronavirus 229E (HCoV-229E). Five cell lines, includingP. abramus andR. sinicus but notT. pachypus cells, were susceptible to human MERS-CoV EMC/2012. However, three tested camel MERS-CoV strains showed different infectivities, with only two strains capable of infecting three and one cell lines respectively. SARS-CoV can only replicate inR. sinicus cells, while HCoV-229E cannot replicate in any bat cells. Bat dipeptidyl peptidase 4 (DPP4) sequences were closely related to those of human and non-human primates but distinct from dromedary DPP4 sequence. Critical residues for binding to MERS-CoV spike protein were mostly conserved in bat DPP4. DPP4 was expressed in the five bat cells susceptible to MERS-CoV, with significantly higher mRNA expression levels than those in non-susceptible cells (P = 0.0174), supporting that DPP4 expression is critical for MERS-CoV infection in bats. However, overexpression ofT. pachypus DPP4 failed to confer MERS-CoV susceptibility inT. pachypus cells, suggesting other cellular factors in determining viral replication. The broad cellular tropism of MERS-CoV should prompt further exploration of host diversity of related viruses to identify its ancestral origin.